Psychological skills training improves exercise performance in the heat - Barwood, M. J.; Thelwell, R. C.; Tipton, M. J. (Medicine & Science in Sports & Exercise, 2008)
Introduction: Fatigue occurs earlier when working at corresponding exercise intensities in hot compared with cool conditions. Psychological skills training (PST) can modify the responses evoked by thermal stimuli such as the respiratory responses on immersion to cold water. This study tested the hypothesis that a 4-d PST package would significantly increase the distance covered during 90 min of running in the heat.